SOCIAL IMMUNITY AND RELIGIOUS AUTHORITY AS MODALITIES FOR BUILDING NON-RADICAL COMMUNITIES IN EASTERN INDONESIA - Muhammad Suaib Tahir; Abdul Syatar (Referensi Islamika: Jurnal Studi Islam, 2026)
This paper examines the role of Islamic education within the Darud Da’wah wal-Irsyad (DDI) network in Eastern Indonesia as a medium for developing social immunity through religious authority and pedagogical practices. The study aims to explore how Islamic education within the DDI network promotes moderate religious understanding, how the authority of teachers and religious scholars regulates religious discourse, and how institutional and cultural mechanisms within Islamic education contribute to building non-radical communities. This research employs a qualitative approach using qualitative content analysis. Data were collected through the examination of educational documents, including curricula and institutional materials, as well as semi-structured interviews with key educational actors such as institutional leaders, teachers, and alumni. The analysis focuses on identifying value orientations, normative assumptions, and social practices that shape moderate religious perspectives. The findings reveal that Islamic education within the DDI network functions as an effective social infrastructure for cultivating social immunity against radicalism. The authority of teachers and religious scholars grounded in scholarly legitimacy and cultural influence plays a central role in translating moderate Islamic values into curricula, daily educational practices, and community-based religious outreach. The study concludes that Islamic educational institutions and religious organizations hold strategic importance in strengthening social resilience and promoting preventive approaches to radicalism that prioritize community development rather than security-centered responses. The originality of this study lies in its conceptualization of Islamic education as a form of “social immunity,” highlighting how religious authority, institutional culture, and pedagogical practices interact to create community-based resilience against radical ideologies, particularly within the educational network of DDI in Eastern Indonesia.